Awareness on Risk Factors and Warning Signs and Belief about Cancer among General Public in a Community of Biratnagar, Morang (Far Western Review, 2023)
Globally, cancer is the leading cause of death and increasing in trend in Nepal. Lack of awareness on cancer, particularly of its risk factors, possible signs and screening guidelines is the barrier for early detection of cancer. Myths and misconceptions related to cancer screening need to be tackled through public health education programs. Hence, this study aims to assess the awareness about cancer risk factors, warning signs, and beliefs about cancer in the general public. Descriptive cross-sectional study design was adopted, and a total of 188 households in a community at Biratnagar-8, Morang were included by using the systematic random sampling. Sampling frame was designed using interval of 17 (Kh interval) to meet the sample size. Face to face interview was conducted to collect data within a 4- week period. Data was analyzed in IBM SPSS version 16, and descriptive statistics such as frequency, percentage, mean were calculated and are presented in tables. Out of the 188 study participants, more than half belonged to 20-35 years age group, with a mean age 45.9 years, and two-thirds (69.7%) were female. The majority (80.9%) of study participants had inadequate awareness on risk factors and warning signs of cancer. However, half of them believed that cancer can be diagnosed at early stages (49.5%) and preventable (46.8%). The study concluded that study participants had inadequate awareness on risk factors and warning signs of cancer. Therefore, there is an urgent need to focus for the development and implementation of public campaigns to increase awareness on cancer.